Media Visual sebagai Alat Bantu Pembelajaran Keterampilan Menulis Teks - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2025)
Writing skills are one of the basic competencies in language learning that require continuous practice and the right approach. One approach that has proven effective is the use of visual media as a learning aid. This literature study aims to analyze the contribution of visual media in improving students' text writing skills, especially at the elementary and secondary education levels. The study was conducted on various national and international studies published in the last ten years. The results of the analysis show that visual media such as serial images, short videos, digital illustrations, and educational comics can stimulate imagination, expand vocabulary, and help structure ideas in writing. Visual media has also proven effective in building students' motivation and interest in writing activities. A visual-based approach makes the writing learning process more contextual, interactive, and meaningful. This study recommends the systematic integration of visual media in the Indonesian language learning curriculum, especially in the development of narrative, descriptive, and expository writing skills. In addition, teachers are expected to be able to innovate in the selection and use of visual media according to the needs and characteristics of students.